Rectal potential difference and histology in Crohn's disease. Issue 4 (April 1977) - Ruddell, W S; Blendis, L M; Lovell, D
Abstract : The rectal potential difference (PD) was measured in 27 patients with Crohn's disease, and in 16 subjects without gastrointestinal disease to establish a normal range. Sigmoidoscopic assessment and rectal biopsy were performed in all patients with Crohn's disease, and the mean resting rectal PD was significantly reduced in patients with sigmoidoscopically active disease and in those with abnormalities of the superficial epithelium on rectal biopsy. Patients with diarrhoea had a significantly lower mean resting PD than those with normal bowel habit, suggesting that an abnormality of rectal sodium transport may be contributing to the diarrhoea in these patients. The response of rectal PD to mineralocorticoid stimulation with oral fludrocortisone was measured in 13 patients. The PD failed to rise only with patients with sigmoidoscopically active disease, and the test proved to be a less sensitive indication of minor mucosal abnormalities than sigmoidoscopy of biopsy.